The role of perioperative transfusion in mortality in geriatric patients with intertrochanteric fracture - Tao Wang; Yubin Long; Zhiqian Wang; Zhiyong Hou (Scientific Reports)
Abstract The primary purpose was to assess the incidence and predictors for mortality in Chinese geriatric patients with perioperative transfusion following intertrochanteric fracture (IF) surgery. A total of 1260 patients who received perioperative transfusion following IF surgery between Jan. 2016 and Dec. 2018 were included. Data was performed to compare the mortality group and the survival group based on subgroup of follow-up time in univariate, and adjusted Cox regression analysis. Perioperative transfusion factors included total, pre-, intra-, and post-operation transfusion volume, and number of transfusions. In our study, the mortality rate was 0.87%, 1.6%, 2.9%, 7.0%, and 13.4% at 30-day, 3-month, 6-month, 1-year, and 2-year follow-up, respectively. Within 6-month follow-up, the adjusted Cox regression analysis revealed that a high American Society of Anesthesiologists (ASA) score, as well as an increase in volume and number of transfusions leading to rapidly increasing morbidity, were identified as risks with mortality. While advanced age and complications played important roles in mortality from 6-month follow-up. In the present study, a high ASA score, as well as the volume and number of transfusions, were identified as risk factors for mortality after IF surgery in Chinese geriatric patients within 6-month follow-up. However, age and severe complications contributed to mortality in 1- and 2-year follow-up.